2015
DOI: 10.4236/ojmi.2015.53017
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Image Prediction Using Principal Component and Multi-Channel Singular Spectral Analysis: A Feasibility Study

Abstract: Respiratory motion induces the limit in delivery accuracy due to the lack of the consideration of the anatomy motion in the treatment planning. Therefore, image-guided radiation therapy (IGRT) system plays an essential role in respiratory motion management and real-time tumor tracking in external beam radiation therapy. The objective of this research is the prediction of dynamic timeseries images considering the motion and the deformation of the tumor and to compensate the delay that occurs between the motion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The dataset involved 569 instances with 32 attributes and 2 classes. They used two essential dimensionality reduction strategies principal component analysis (PCA) and linear discriminant analysis (LDA) and showed that kNN with LDA technique worked better than kNN and kNN with PCA with the accuracies 97.06%, 95.29%, and 95.88% [21]. Separately, NB techniques in combination with a weighting approach has been deployed in [22], yielding a BC prediction accuracy of 98.54%.…”
Section: Related Workmentioning
confidence: 99%
“…The dataset involved 569 instances with 32 attributes and 2 classes. They used two essential dimensionality reduction strategies principal component analysis (PCA) and linear discriminant analysis (LDA) and showed that kNN with LDA technique worked better than kNN and kNN with PCA with the accuracies 97.06%, 95.29%, and 95.88% [21]. Separately, NB techniques in combination with a weighting approach has been deployed in [22], yielding a BC prediction accuracy of 98.54%.…”
Section: Related Workmentioning
confidence: 99%
“…This study was inspired by our previous work in which we reported a feasibility study on tracking moving tumors using dynamic image prediction [10]. In this study, we report a more practical approach involving collection of the available imaging datasets.…”
Section: Introductionmentioning
confidence: 99%